Regulatory in the Pharmaceutical Industry - Madalaimuthu, Malvika Mishra (Journal of Social Science and Humanities, 2025)
Regulatory Affairs (RA) is a crucial profession in pharmaceuticals, medical devices, and biotechnological industries, encompassing scientific and legal aspects of drug development. It helps companies avoid issues and ensures commercialization. RA faces challenges like geopolitical shifts, green economy, and COVID-19, impacting new therapies and their role.[1] Drug Regulatory Affairs (DRA) is a crucial unit in pharmaceutical companies, providing strategic, tactical, and operational support to expedite the development and delivery of safety and efficacy in pharmaceuticals, veterinary medicines, medical devices, pesticides, agrochemicals, cosmetics, and healthcare products. The Indian pharmaceutical industry is one of the fastest-growing in the country, with a compounded annual growth rate of over 13% in the last 5 years.[2] The US Food and Drug Administration and European Medicines Agency offer opportunities to expedite drug development and regulatory approval timelines. The 1950s pharmaceutical tragedies, including thalidomide, vaccination, and sulfanilamide elixir, led to expanded laws, tougher standards for Good Manufacturing Practices, and increased regulatory scrutiny in the USA, Europe, and India. Drug registration is regulated through development and commercialization, but marketing can be challenging. Regulatory bodies handle executive law, nonsupervisory law, secondary legislation, and rulemaking. Independent regulatory agencies are created for quick application, complexity, and political interference, conducting audits, investigations, and imposing restrictions. The drug regulatory affairs (DRA) professional is crucial in pharmaceutical research and development, ensuring regulatory compliance with the Food and Drug Act and TPP Guidelines/Policies. They secure approval from Health Canada's Therapeutic Products Programme, require excellent writing and communication skills, and can effectively negotiate favorable labeling. The RA plays a crucial role in various systems, often as a part-time or full-time employee.[3] The number of RAs and their skill situations depend on the size of the design, perceived complexity of conditions, and available resources. RAs should be considered crucial contributors, requiring a unique mix of knowledge, real-world experience, and ability to interpret and satisfy guests', druggies', and operation's intent.[4] The regulatory department is responsible for ensuring manufacturers follow global legislative and regulatory requirements at every stage of the drug development process, from research to marketing. They keep track of updated legislatives globally and advise on legal and scientific restraints. Regulatory affairs professionals collect, understand, and identify scientific and clinical data for regulatory submissions. They also provide strategic and technical advice to functional areas, including medical affairs, clinical development, and commercial marketing. They also ensure accurate records and documentation, as annual reports are required for submissions to the FDA or other governmental agencies.[5]